The Training of Reading Beam Notations on Pranada Lines for Children in the Community Reading Park - Syaida Oktira, Yona; Efendi, Nofriza (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2022)
Block notation is one of the elements in music. Creativity in singing needs to be trained from an early age, with interest and talent, creativity is also very influential with experience. The purpose of this community service implementation is to provide training to read block notation on the rhyme line for children at the community reading park (TBM) in order to children are accustomed to seeing block notation from an early age, students are able to differentiate the tone